Biodiversity and evolution of parasitic life in the Southern Ocean - Klimpel, Sven; Kuhn, Thomas, 1982-; Mehlhorn, Heinz (Springer, 2017)
The Southern Oceans including Antarctic regions are peculiar and very sensitive water biotopes, where animal life and species interrelations are only poorly investigated. Especially the influence of parasites on their host species needs intensive consideration in times of global warming and worldwide pollution. Both factors may influence the finely balanced interrelationships between parasites and endangered hosts especially in specialized regions such as Antarctica. Before this background the present book offers a broad spectrum of important parasite-host interrelations in times of ecosystem changes written by experienced and renown international specialists.- Resumé vydavatel
7.8 Anisakids as€Indicators of€Trophic Web Stability and€Habitat Disturbance of€Marine Ecosystems from€the€Austral Region.
Keywords: parazitické organismy -- Antarktický oceán; parazitologie -- Antarktický oceán; biodiverzita -- Antarktický oceán; klimatické změny -- Antarktický oceán; parazit a hostitel -- Antarktický oceán; parasitic organisms -- Southern Ocean; parasitology -- Southern Ocean; biodiversity -- Southern Ocean; climate changes -- Southern Ocean; parasite and host -- Southern Ocean; elektronické knihy; sborníky; electronic books; papers of several authors